Relationships between Personality and Burn-Out: An Empirical Study with Helping Professions' Workers - Magnano, Paola; Paolillo, Anna; Barrano, Carmine (International Journal of Humanities and Social Science Research, 2015)
Stress-related illnesses, such as burnout, had an increase over the last decade, even though not every employee, in the same workplace, shows burnout symptoms, suggesting that individual factors may contribute to this phenomenon. In fact, even though research on burnout generally has tended to explore the organizational factors associated with this condition, which play certainly an important role, however we cannot ignore the relationship between burnout and personality. This study explored the relationship between personality and burn-out in 144 helping professions' workers. Personality was measured by the Big Five Questionnaire; burn-out was measured by the Link Burn-out Questionnaire. Results confirm a relationship between the two constructs, partially supporting previous research that explained burn-out not only by organizational factors, but also by individual dimensions.